CHALLENGING OBJECTIFICATION THROUGH ALTERNATIVE BEAUTY CONCEPTS IN THE FILM I FEEL PRETTY (2018) - Difa Mahya Zahara; Nina Farlina (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2023)
Beauty ideals that primarily focus on physical attributes play the role of a cultural milieu in which women are vulnerable to objectification. Such a cultural force gives rise to the importance of investigations on literature, such as films, as a cultural product as well as a cultural shaper in which women are portrayed and represented through their narrative, characters, and more. This study is a qualitative descriptive study on the film I Feel Pretty that applies the feminist theory of objectification. It aims to explore the portrayal of Renee Bennett, the main character, in dealing with objectifying beauty ideals and how such phenomena are challenged in the film. The results found that Renee Bennett experiences objectification by others, self-objectification, and objectifying others under the context of appearance-focused beauty concepts. However, the film challenges such objectifying beauty concepts by introducing alternatives that focus on internal qualities or non-physical attributes, such as self-confidence, intelligence, and health. Thus, the film is a critique towards the existing beauty ideals that glamorize the physique, and it encourages a shift of focus from external to internal qualities that support women’s mobility and well-being.